Vitrification of Mesenchymal Stromal Cells in Alginate Microbeads - Zaykov, V. S.; Petrenko, Yu. A.; Trufanova, N. A.; Pravdyuk, A. I.; Petrenko, A. Yu. (Problems of Cryobiology and Cryomedicine, 2024)
Cryopreservation of cells encapsulated in alginate microbeads is one of the important issues of tissue engineering. The present study was directed on the estimation of the effect caused by of duration of alginate encapsulated mesenchymal stromal cells (MSCs) exposure in multicomponent cryoprotective solution DEPS-1 (10% DMSO, 20% EG, 20% 1,2-PD and 0.5 M sucrose) on survival and metabolic activity after vitrification and rewarming. It was shown using of multicomponent cryoprotective solution and stepwise exposure allowed to achieve successful cryopreservation by means of vitrofication of MSCs encapsulated in alginate microspheres. The main difference between vitrification of MSCs encapsulated in microspheres vs. single cells was the longer exposure with CPA.